2022
DOI: 10.1155/2022/6244175
|View full text |Cite|
|
Sign up to set email alerts
|

OX40-Fc Fusion Protein Alleviates PD-1-Fc-Aggravated Rheumatoid Arthritis by Inhibiting Inflammatory Response

Abstract: Background. Researches have confirmed that the abnormal signals of OX40 and PD-1 lead to the changes of T cell biological behavior, thus participating the immunopathological process of RA. However, the pathogenesis of RA immunopathological process has not been clarified yet. Methods. 30 DBA/1 mice were randomly divided into 5 groups (6 mice per group): control group, collagen-induced arthritis (CIA) group, PD-1-Fc/CIA group, OX40-Fc/CIA group, and PD-1-Fc + OX40-Fc/CIA group. The pathological changes in mice j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Since the first description in 1989 of CD4-Fc-fusion antagonists that inhibit human immune deficiency virus entry into T cells, Fc-fusion proteins have been intensely investigated for their effectiveness to curb a range of pathologies. In the treatment of human diseases, Fc-fusion strategies have been used in therapy including experimental and clinical drugs (21)(22)(23). Fusion proteins based on the immunoglobulin Fc domain show the ability to facilitate protein expression and enable easy purification of recombinant protein by protein A chromatography (24).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description in 1989 of CD4-Fc-fusion antagonists that inhibit human immune deficiency virus entry into T cells, Fc-fusion proteins have been intensely investigated for their effectiveness to curb a range of pathologies. In the treatment of human diseases, Fc-fusion strategies have been used in therapy including experimental and clinical drugs (21)(22)(23). Fusion proteins based on the immunoglobulin Fc domain show the ability to facilitate protein expression and enable easy purification of recombinant protein by protein A chromatography (24).…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes in synovial fluid and synovial tissue from RA patients express OX40, and OX40L is expressed on sub-lining cells in synovial tissue [ 9 ]. OX40-Fc fusion protein alleviates PD-1-Fc-exacerbated RA by suppressing the inflammatory response [ 10 ]. In addition, OX40 plays a pathogenic role in the development of autoimmune arthritis as an alternative co-stimulator of CD4 + CD28 − T cells, suggesting it as a potential target for immunomodulatory therapy in RA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%